Factors Predicting Self-Care Behaviors among Low Health Literacy Hypertensive Patients Based on Health Belief Model in Bushehr District, South of Iran - Azam Larki (International Journal of Hypertension, 2018)
The aim of this study was to determine the factors influencing adherence to self-care behaviors among low health literacy hypertensive patients based on health belief model. A cross-sectional study was conducted among 152 hypertensive patients with low health literacy. Patients with limited health literacy were identified by S-TOFHLA. The data were collected using H-scale for assessing self-care behaviors and, HK-LS for assessing knowledge of hypertension. A researcher-made questionnaire was applied for collecting data of health belief model constructs. Data were analyzed by SPSS version 22 with using multiple logistic regression analyses. Perceived self-efficacy was associated with all self-care behaviors except medication regimens. There was a significant association between perceived susceptibility and adherence to both low-salt diet (OR = 3.47) and nonsmoking behavior (OR = 1.10). Individuals who had more perceived severity (OR = 1.82) had significantly greater adherence to their medication regimens. Perceived benefits and barriers were not significantly associated with either type of hypertension self-care behaviors. It seems that designing and implementation of educational programs to increase self-efficacy of patients and promote their beliefs about perceived susceptibility and severity of complications may improve self-care behaviors among low health literacy hypertensive patients.